Effects of silicon doping on strengthening adhesion at the interface of the hydroxyapatite–titanium biocomposite: A first-principles study; Computational Materials Science; Vol. 159 - Grubova I. Yu. Irina Yurievna; Surmeneva M. A. Maria Alexandrovna; Huygh Stijn; Surmenev R. A. Roman Anatolievich; Neyts E. C. Erik (2019, 2019)
Title screen